Degenerate Nonlinear Boundary Value Problems for Fully Nonlinear Elliptic Equations of Second Order (Journal of Partial Differential Equations, 2020)
In this paper, we will consider the degenerate nonlinear boundary value problems for nonlinear elliptic equations. We extend Lieberman & Trudinger's results from nondegenerate oblique derivative boundary values to degenerate boundary values.
Keywords: Degenerate; nonlinear; estimate; elliptic equation